Predicting clinical outcome by indexed mitral valve tenting in functional mitral valve regurgitation. Issue 1 (24th January 2021) - von Stumm, Maria; Dudde, Florian; Holst, Theresa; Sequeira-Gross, Tatjana; Pausch, Jonas; Müller, Lisa; Sinning, Christoph R; Reichenspurner, Hermann; Girdauskas, E
Abstract : Objectives: Mitral valve (MV) tenting parameters are indicators of left ventricular remodelling severity and may predict outcome in functional mitral regurgitation (FMR). We hypothesised that indexing of MV tenting area to body surface area (BSA), to mitral annulus diameter or gender-adjusted analysis of tenting parameters may improve their prognostic value. Methods: We identified retrospectively 240 patients with consecutive FMR (mean age 68±10 years; men=135) from our institutional database who underwent isolated MV annuloplasty during a period of 7 years (2010–2016). Using preoperative two-dimensional transthoracic echocardiographic images, MV tenting parameters including tenting area, tenting height and annulus diameter were systematically assessed. Follow-up protocol consisted of chart review and structured clinical questionnaire. Primary study endpoint was the composite of death and adverse cardiac events (ie, MV reoperation, cardiac resynchronisation therapy implantation, ventricular assist device implantation or heart transplantation). Results: BSA-indexed MV tenting area was identified as independent predictor of primary study endpoint (HR 1.9; 95% CI 1.1 to 3.5; p=0.02). After cut-off point analysis, BSA-indexed MV tenting area >1.35 cm 2 /m 2 was significantly associated with primary study outcome (HR 2.3; 95% CI 1.3 to 4.0; p=0.003). Annulus-indexed MV tenting area showed only a tendency towards primary study endpoint prediction (HR 2.8; 95% CI 0.6 to 12.6; p=0.17). Between female and male patients, BSA-indexed MV tenting area was similar (1.42±0.4 cm 2 /m 2 vs 1.45±0.4cm 2 /cm 2 ; p=0.6) and gender was not associated with primary study outcome (HR 0.8; 95% CI 0.5 to 1.4; p=0.5). Conclusion: In our FMR cohort, BSA-indexed MV tenting area showed the strongest association with negative outcomes following isolated MV annuloplasty. Patients with BSA-indexed MV tenting area >1.35cm 2 /m 2 could potentially benefit from additional surgical maneuvers addressing left ventricular remodelling.